Trema domingensis rises like a Phoenix from the ashes of Trema integerrima: a reassessment of the entire-leaved species of neotropical Tream (Cannabaceae) - Garwood, Nancy C.; Jordan, Kristina; Flowers, Nicholas D.; Humphreys, Aelys M.; Russell, Stephen J.; Neubig, Kurt M. (Journal of the Botanical Research Institute of Texas, 2018)
We resolve three problems concerning the three entire-leaved species of Neotropical Trema. 1) Phylogenetic and morphological results showed that T. integerrima (Beurl.) Standl., T. domingensis Urb., and T. laxiflora Lundell are a single species; therefore, we combine them under a single name. 2) The date of publication gives priority to T. integerrima, as the basionym Sponia integerrima Beurl. was published in 1856. However, the type specimen, Billberg 308 (S), is not a species of Trema but Pouzolzia obliqua (Wedd.) Wedd. (Urticaceae); therefore, Sponia integerrima Beurl. is a new synonym of P. obliqua. The next available name for the entire-leaved species is T. domingensis, published in 1912. 3) The type of T. domingensis, Fuertes 312, is a mixed collection. Specimens of Fuertes 312 held at B, NY, U, and USD are T. domingensis, while those at P, G, US, and Z are Celtis trinervia Lam. We provide a historical review to understand how these problems arose and persisted unnoticed for decades.